Alternating Incubation Effects in the Generation of Category Exemplars. (19th May 2015) - Smith, Steven M.; Gerkens, David R.; Angello, Genna
Abstract: Four experiments tested the forgetting fixation hypothesis of incubation effects, comparing continuous vs. alternating generation of exemplars from three different types of categories. In two experiments, participants who listed as many members as possible from two different categories produced more responses, and more novel responses, when they alternated back and forth between the two categories, as compared to continuous uninterrupted listing from each of the two categories. This incubation effect was not found in Experiment 1, when participants were given taxonomic categories ( birds and clothing ) for the generation task, but was found in Experiment 2 with sense impression categories ( cold things and heavy things ), and in Experiment 3 with ad hoc categories ( equipment you take camping and fattening foods ). A similar incubation effect was observed in Experiment 4 when a non‐verbal task was given between category generation tasks, but only for flexibly defined categories. The results suggest that forgetting from one alternating listing period to the next in the form of altering category cue representations was consistent with the observed incubation effects. These alternating incubation effects have implications for understanding cognitive processes that underlie creative cognition.